Methotrexate-loaded liposomal formulation enables 6-week sustained intraocular therapeutic drug release in a porcine model - Hammer, Maximilian; Skrzypczyk, Lea; Wohlfart, Sabrina; Ackermann, Bryan Calder; Geisweid, Ludwig; Pohl, Simon William; Karaivanova, Margarita; Herth, Jonathan; Augustin, Victor A.; Studier-Fischer, Alexander; Sackmann, Tina; Kaulen, Leon D.; et al. (Advanced healthcare materials, 2025)
Methotrexate (MTX) inhibits cell proliferation, which underlies ocular diseases, including intraocular lymphoma and proliferative vitreoretinopathy. However, MTX normally requires bi-weekly intravitreal injections due to a short half-life, causing rapid clearance below therapeutic thresholds within 72h. To overcome these limitations, sustained-release carriers, including poly(lactic-co-glycolic) acid-based implants, were investigated in vitro previously. These systems offer prolonged drug delivery but require relatively large-gauge surgical implantation, which increases the risk of surgical complications and limits their practical use. In this study, MTX-loaded liposomes that can be administered via a 30-gauge cannula are developed, obviating the need for more invasive surgical implantation. This phospholipid-based liposomal formulation succeeded in enabling sustained methotrexate release at therapeutic levels for over six weeks following a single intravitreal injection, demonstrated in vivo in a large animal pig model. High biocompatibility of this novel liposomal formulation is confirmed through longitudinal retinal structure (optical coherence tomography) and function (electroretinography) assessments. This liposomal formulation of MTX provides a clinically and surgically optimized drug delivery system that allows improved management of intraocular lymphoma and proliferative vitreoretinopathy in the future.
Erstmals veröffentlicht: 25. September 2025
Gesehen am 16.10.2025